An Implementation with Low Impact Development (LID) Techniques within the Scope of Sustainable Stormwater Management: An Example of Mass Housing Project - Müftüoğlu, Volkan; Perçin, Halim (Peter Lang Publishing Group, 2021)
Stormwater, which is tried to be rapidly collected from urban lands, is transferred to receiving waters in an uncontrolled manner, and this situation causes the receiving waters, and thus the entire water cycle to be negatively affected in terms of pollution, especially with the sediment and heavy metals carried by runoffs. Traditional stormwater management solutions in our cities are often inadequate in terms of size and capacity, and even fail to fully accomplish their purpose because of accumulated sediment and pollutants, as a result of excessive rainfall in a short amount of time due to global warming in recent years. On the other hand, sustainable stormwater management approaches, in which natural solutions are prioritized, aim to solve the stormwater problem at its source as much as possible and to store the water that will pass through the runoff or infiltrate it to groundwater. The widespread use of sustainable stormwater management solutions in our cities will provide rain harvesting, which can be a solution to water shortages due to drought, and will support traditional stormwater management solutions during excessive rainfalls. In this context, this study aims to propose appropriate stormwater solutions on a mass housing project with the lid approach one of sustainable stormwater management approaches, and to reveal the contribution of these solutions in stormwater management. It was concluded that the continuation of the sample area, which is managed with integrated management practices within the scope of lid approach, by preserving the pre-development hydrological conditions, is very important in terms of ensuring safer habitats and the sustainability of the waterstormwater cycle in the sample area.
Keywords: Ankara gölbaşi yaylabağ yaylaşehir mass housing project; Ecological stormwater management; Integrated management practices; Low impact development; Runoff; Water cycle